Interaction Strategies for Effective Augmented Reality Geo-Visualization: Insights from Spatial Cognition. (4th March 2021) - Gardony, Aaron L.; Martis, Shaina B.; Taylor, Holly A.; Brunyé, Tad T.
Abstract : Standalone augmented reality (AR) systems have great potential for interactive three-dimensional (3D) geo-visualization. Emerging head-worn AR technologies can display rich graphical imagery of large-scale environments and permit intuitive interaction through gestural and voice inputs. Yet, how users engage in geo-visualization through these interfaces and what interaction strategies yield the best spatial memory and navigation performance remain open questions. In the present empirical investigation, we related user interactions in a 3D geo-visualization application implemented on the Microsoft HoloLens AR system to virtual navigation outcomes. Informed by spatial cognitive theory, we uncovered interaction strategies during goal-oriented study of a 3D urban environment that predicted different aspects of navigation performance. Users who positioned the 3D city model to gain an overhead (i.e. survey perspective) view early on performed best when later following the route from memory. In contrast, consistent interaction switching (i.e. perspective transformation) during study predicted navigational efficiency when participants were unexpectedly tasked to return to the origin of the route. Individual differences also related to aspects of user interaction. Implications for 3D geo-visualization and navigation-assistive AR application design and suggestions for future directions are discussed.